THE USABILITY EVALUATION OF ONLINE TRAINING PLAGIARISM MODULE USING ICCEE APPROACH FOR ACADEMIC WRITING BEGINNERS - Hafizhah Suzana Hussien; Fariza Khalid; Supyan Hussin; Mohamad Taha Ijab; Dini Farhana Baharudin; Ahmad Najmi Ismail (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
THE USABILITY EVALUATION OF ONLINE TRAINING PLAGIARISM MODULE USING ICCEE APPROACH FOR ACADEMIC WRITING BEGINNERS Plagiarism is one of the issues commonly observed in academia, particularly in academic writing. Academic writing is challenging, especially for beginners who have just begun to learn how to write a research-oriented article. Compared to other genres of writing, academic writing has its own rules and organization. Previous studies have shown that students tend to plagiarize when writing their academic papers. The existing modules that serve as a reference for academic writing are lacking in content which emphasizes the importance of academic integrity. Realizing this phenomenon, a module called the Online Training Plagiarism Module was developed using the Identify-Choose-Create-Engage-Evaluate (ICCEE) approach in order to help beginners to write good papers with integrity and avoid plagiarism. A survey approach was used in this study to evaluate the usability of the Online Training Plagiarism Module. A total of 70 first year postgraduate students participated in this study and those students can be categorized as beginners in academic writing A usability questionnaire adapted based on USE instrument was used to assess four aspects, which are usefulness, ease of use, ease of learning, and satisfaction. The findings show that the usability level of the proposed module is high among the beginners. Therefore, using the Online Training Plagiarism Module for academic writing beginners is both relevant and acceptable, allowing beginners to use it as a reference in academic writing courses.